The Use of Storybooks with Science Pillars to Increase Children's Curiosity - Sulistyowati Sulistyowati; Naning Kurniawati (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to describe the improvement of children's curiosity after the implementation of science based pillars in learning activities at RA Fattahul Huda Pungpungan. The method used is qualitative descriptive with a focus on changes in children's behavior before and after using science-based storybooks. The findings indicate that before the intervention, children tended to be passive, asked fewer questions, and had not shown a strong interest in exploratory activities. After using storybooks with science pillars, there was a significant increase in aspects such as active questioning, observation skills, tendency for independent exploration, and the ability to retell simple phenomena found in the stories. Visual and narrative stimuli in the storybooks proved capable of stimulating children's learning motivation and curiosity, thus supporting the development of early science literacy. These findings reinforce the views of Piaget, Vygotsky, and Bruner regarding the importance of visual stimuli, social interaction, and direct experience in developing children's cognitive abilities.